Apple tree adaptation to shade in agroforestry: an architectural approach. Issue 5 (2nd May 2021) - Pitchers, Benjamin; Do, Frédéric C.; Pradal, Christophe; Dufour, Lydie; Lauri, Pierre‐Éric
Abstract : PREMISE: The expression of shade adaptation traits is expected to be stronger in low light and can be detrimental to flowering and yield. Our study focused on the expression of shade adaptation traits of apple trees ( Malus domestica Borkh. 'Dalinette') in an agroforestry system. METHODS: The architecture of 45 apple trees in their third and fourth year was extensively described and analyzed at the tree scale and compared depending on the light quantity received during the growing season. Flower cluster phenology and the relation between leaf area and floral initiation were also investigated. RESULTS: The number of growing shoots and the leaf area were reduced by shade even if specific leaf area increased with increasing shade. Shade did not modify primary growth but did decrease secondary growth, so that apple tree shoots in shade were slender, with a lower taper and reduced number and proportion of flower clusters. The correlation between floral initiation and leaf area was high both in full and moderate light but not for apple trees in low light. Shade did not impact the date of bud burst and the early phenological stages of flower clusters, but it reduced the number of days at full bloom. CONCLUSIONS: Our results suggest that while the architecture of apple trees is modified by a reduction in light intensity, it is not until a reduction of 65% that the capability to produce fruit is impeded. These results could help optimize the design of apple‐tree‐based agroforestry systems.